2019
DOI: 10.1186/s12935-019-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NPL4 promotes bladder cancer cell proliferation by inhibiting DXO destabilization of cyclin D1 mRNA

Abstract: Background NPL4 is an important cofactor of the valosin-containing protein (VCP)–NPL4–UFD1 complex. The VCP–NPL4–UFD1 has been considered as a ubiquitin proteasome system (UPS) regulator and response to protein degradation. While NPL4 plays important roles in various diseases, little is known about its functions in bladder cancer (BC). Methods MTT assays and colony forming test were performed to evaluate cell proliferation ability and Western blotting was used to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In this paper, NPL4 aggregation with its increased intensity was also indicated in 786-o cells after disulfiram treatment. Moreover, Lu et al showed that NPL4 was upregulated in bladder cancer tissue and was correlated with poor prognosis; NPL4 knockdown was found to decrease bladder cancer cell proliferation by reduction of cyclin D1 expression [ 27 ]. Because NPL4 is the most important cofactor of p97, NPL4, which can be targeted by disulfiram, is also a key molecule for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, NPL4 aggregation with its increased intensity was also indicated in 786-o cells after disulfiram treatment. Moreover, Lu et al showed that NPL4 was upregulated in bladder cancer tissue and was correlated with poor prognosis; NPL4 knockdown was found to decrease bladder cancer cell proliferation by reduction of cyclin D1 expression [ 27 ]. Because NPL4 is the most important cofactor of p97, NPL4, which can be targeted by disulfiram, is also a key molecule for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…upregulated in bladder cancer tissue and was correlated with poor prognosis; NPL4 knockdown was found to decrease bladder cancer cell proliferation by reduction of cyclin D1 expression [27]. Because NPL4 is the most important cofactor of p97, NPL4, which can be targeted by disulfiram, is also a key molecule for the treatment of cancers.…”
Section: Plos Onementioning
confidence: 99%
“…Hyperosmotic stress induces phase separation of proteasome-containing nuclear foci (containing ubiquitinated proteins, VCP, and several proteasome-related proteins), which collectively constitute a proteolytic site ( Yasuda et al, 2020 ). Compared to normal cells, cancer cells are characterized with upregulation of the VCP-UFD1-NPLOC4 pathway to digest false-synthesized and misfolded proteins ( Tsujimoto et al, 2004 ; Yamamoto et al, 2004 ; Huiting et al, 2018 ; Lu et al, 2019 ). Thus, inhibition of the VCP-UFD1-NPLOC4 pathway may represent as a selective treatment option for cancer.…”
Section: Er-associated Degradation: a Quality-controlled Degradation Of Misfolded Proteinsmentioning
confidence: 99%
“…It has been revealed that cell proliferation was increased by DXO downregulation and destabilizing cyclin D1 mRNA in bladder cancer. However, genes controlled by this transcription factor have not yet been identified, indicating that more research is required to be performed [60].…”
Section: Discussionmentioning
confidence: 99%